Abrupt, climate-induced increase in wildfires in British Columbia since the mid-2000s - Parisien, Marc-André; Barber, Quinn E.; Bourbonnais, Mathieu L.; Daniels, Lori D.; Flannigan, Mike D.; Gray, Robert W.; Hoffman, Kira M.; Jain, Piyush; Stephens, Scott L.; Taylor, Steve W.; Whitman, Ellen (Communications earth & environment, 2023)
In the province of British Columbia, Canada, four of the most severe wildfire seasons of the last century occurred in the past 7 years: 2017, 2018, 2021, and 2023. To investigate trends in wildfire activity and fire-conducive climate, we conducted an analysis of mapped wildfire perimeters and annual climate data for the period of 1919–2021. Results show that after a century-long decline, fire activity increased from 2005 onwards, coinciding with a sharp reversal in the wetting trend of the 20th century. Even as precipitation levels remain high, moisture deficits have increased due to rapid warming and increased evaporative demand. Bottom-up factors further influence fire activity, as the legacy of past wildfires, insect outbreaks, and land-use practices continually influence fire regimes. The compound effects of climate-induced moisture changes and altered fuels now force British Columbians to confront the harsh reality of more frequent years of intense and prolonged wildfire activity.